Being Maniq. Issue 2 (June 2015) - Kricheff, Daniel Abraham; Lukas, Helmut
<x content-type="archive" xml:space="preserve">Abstract</x> This paper, based on ongoing fieldwork among the Maniq people of the Banthat mountain range of Thailand, aims to consider aspects of their culture and practice which allow them to share a mutually coherent system of beliefs and practices over time, despite a noted absence of religious dogma and the subtlety of their ritual practices. It considers how the Maniq themselves describe cosmology, ethnic identity and material practice as being ineluctably linked within their own system of values and beliefs. Such a perspective may also point toward a useful analytical path for outside interpretation, helping to overcome some of the vexing problems hunter-gatherer ritual systems and practices often present for formal analysis.